Management of severe maxillary discrepancy in unilateral cleft lip and palate: six year follow up in a patient with tongue graft - Thapa, Amrit; Sahoo, Nanda Kishore; Jayan, Balakrishnan; Chopra, Sukhbir Singh; Kumar, Andrews Navin (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
The purpose of this original case study was to present the efficiency of combined orthodontic and distraction osteogenesis (DO) in severe maxillary hypoplasia along with importance of tongue graft for closure of large residual palatal defect. DO has been successfully chosen in lengthening and widening the maxilla transversely to relieve anterior dental crowding and transverse discrepancies between the dental arches. A UCLP (unilateral cleft lip and palate), 15 year old male with the chief complaint of esthetic and functional problems because of skeletal class III malocclusion with anterior crossbite and severe midline shift was taken up for this modality of treatment. Considering the severity of malocclusion, combined orthodontic and DO treatment was considered adequate which was likely less invasive and equally stable procedure. RED (rigid external distractor) was used for distraction after initial alignment followed by closure of residual large palatal defect with tongue graft. Result obtained was esthetically good with acceptable occlusion considering the severity with pleasing soft tissue profile. The review was done after six year which showed remarkable skeletal stability with no dehiscence of tongue graft in palate area. The combined use of DO and orthodontic correction in ULCP case had substantial skeletal stability, improving patient esthetic and self-esteem.